Stability of MHD Unsteady Nanofluid Flow through Expanding or Contracting Channel with Permeable Walls. (2017) - Rahman, M.K.; Alam, Md. S.; Khan, M.A.H.
Abstract: The objective of the present study is to investigate the influence of external magnetic field on unsteady incompressible flow of water based nanofluid through a successively expanding or contracting channel with porous walls. The basic governing equations with boundary conditions are non-dimensionalized using appropriate transformation to ordinary differential equations, which are then solved using power series with the help of Hermite-Padé approximation method. The bifurcation diagrams of velocity field and wall shear stress are gained which signifies the stability of the flow. The regular effects of the different governing physical parameters specifically Hartmann number, volume friction of nanoparticles, non-dimensional wall dilation rate and permeation Reynolds number on velocity profiles are depicted graphically.